The girl who wrote in silk - Estes, Kelli (Sourcebooks Landmark, 2015)
Inara Erickson's discovery of an elaborately stitched piece of fabric in her deceased aunt's island estate leads her to the century-old story of Mei Lien, and a difficult truth about her about her family.